1973
DOI: 10.1177/001316447303300412
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Behavioral Attributes of Children Using Multiple Teacher Judgments of Pupil Characteristics

Abstract: EDUCATIONAL AND PSYCHOLOGICAL MEASUREMENT 1973, 33, 859-874. , THE objective of this investigation was (a) to develop an interval scale of measurement for attributes assessing several nonintellectual behaviors of children and (b) to anchor each scale by having teachers assign scale values to behavior descriptors of children possessing the attributes to varying degrees. Attempts to capitalize on the teacher's long term observation of her class members in the development of rating scales have a long history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The work of Lambert and her colleagues (Lambert, 1972;Lambert & Hartsough, 1973;Lambert, Hartsough, & Zimmerman, 1976) provides a substantial body of evidence from which to propose a threedimensional model of nonintellectual behaviors of school-age children -that is, three relatively independent aspects of the affective life of children which can be distinguished. In this model, the dimensions defined are (a) behaviors reflecting adaptation to school, (b) individual differences in emotional states, and (c) individual differences in interpersonal behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Lambert and her colleagues (Lambert, 1972;Lambert & Hartsough, 1973;Lambert, Hartsough, & Zimmerman, 1976) provides a substantial body of evidence from which to propose a threedimensional model of nonintellectual behaviors of school-age children -that is, three relatively independent aspects of the affective life of children which can be distinguished. In this model, the dimensions defined are (a) behaviors reflecting adaptation to school, (b) individual differences in emotional states, and (c) individual differences in interpersonal behavior.…”
mentioning
confidence: 99%
“…A revision of the behavioral rating used in the studies by Lambert et al (1976) provided interval (rather than Likerttype) scales for 11 attributes designed to assess this three-dimensional model of affective characteristics. The development and validation of this scale is reported in Lambert and Hartsough's (1973) article; Hartsough (Note 2) has presented a detailed analysis of the underlying dimensionality of the scale. She reported that the three dimensions of adaptation and interpersonal (aggressive, acting out) and in-trapersonal (withdrawn, shy) adjustment characterized the affective behavior of elementary school children.…”
mentioning
confidence: 99%
“…The schedule is best seen as a measure of teacher perception of pupil adjustment'' (Varlaam et al, 1983, p. 10). Although Lambert and Hartsough (1973) suggest that behavioural ratings by teachers generally compare well with other independent judgements of psychologists and psychiatrists, numerous studies show low levels of agreement between the ratings of parents and teachers. This reflects not only an ''eye of the beholder'' effect (Ghodsian, 1977) but also the situational specificity of behaviour ( Jaycox and Repetti, 1993), for example children with difficult home lives may show fewer problems at school (Smith and Prior, 1995;David et al, 1996).…”
Section: Perceptions Of Child Health/adjustment and Family Processmentioning
confidence: 92%
“…This may reflect true variations in a child's behaviour at school compared with home, psychological distress being particularly evident at home among children living in ''step'' households, for whom the arrival of a new parent-figure has created upheaval or a reduction in parental attention (Richards, 1995). However, as teacher ratings differ according to variables such as a child's sex, ethnic group membership and IQ (Lambert and Hartsough, 1973), it is possible that bias could also occur in respect of known family structure; a single parent being more ''visible'' to the school than ''step'' parent households.…”
Section: Family Life and Child Health And Adjustmentmentioning
confidence: 99%
“…Behavioural Judgements: a comparison of two teacher rating scales PAQUITA McMICHAEL Comparative research on behaviour rating scales designed to select maladjusted children for intervention or for epidemiological purposes has tended to concentrate on variations between respondents (parents, teachers, clinicians) in completing the same scale (Wickman, 1928;Mitchell & Shepherd, 1966;Schanberger, 1968;Ziv, 1970;Lambert & Hartsough, 1973). Their discrepant judgements, it is suggested (Tizard, 1968) lead to serious over-inclusion of children in the maladjusted category if only one measure of behaviour is used.…”
mentioning
confidence: 99%